Does the topology of the river network influence the delivery of riverine ecosystem services?. (18th September 2020) - Karki, Seema; Stewardson, Michael J.; Webb, James Angus; Fowler, Keirnan; Kattel, Giri Raj; Gilvear, David J.
Abstract: Riverine ecosystems provide important ecosystem services reflecting their unique forms and functions. While the effects of stressors such as land cover change, climate change and growing economies on riverine ecosystem services (RES) have been well researched, the effect of the structure of the river network itself is less understood. This paper compares the capacity of different river network topologies in the delivery of selected RES. For three contrasting synthetic river network topologies (Long Trellis Narrow; Coastal Dendritic; Inland Dendritic), we applied simple functional equations to model six RES: water supply, hydropower generation, sediment retention, nutrient uptake, flood attenuation and aquatic habitat provision. Results showed that the synthetic topologies deliver different levels of RES, driven by their differences in physical structure. For example, the Inland Dendritic network removed more nitrate and better attenuated flooding due to its relatively longer lower reaches but offered poorer prospects for water supply because the longer reaches were more susceptible to transmission losses (e.g., due to bed seepage). This study provides a valuable first step in understanding the effect of river network topology on RES delivery, and the relative strengths among network types. Understanding these effects can aid decision makers in the conservation and restoration of degraded river basins to preserve RES for future generations.